2006
DOI: 10.1158/1078-0432.ccr-06-1330
|View full text |Cite
|
Sign up to set email alerts
|

SD-1029 Inhibits Signal Transducer and Activator of Transcription 3 Nuclear Translocation

Abstract: Purpose: Signal transducer and activator of transcription 3 (Stat3) proteins have important roles in cancer cell survival and proliferation. Recent studies show that aberrant Stat3 activation promotes tumor growth and survival in several human cancers, and thus, presents an attractive pathway for the development of targeted anticancer therapy. Stat3 is a DNA-binding transcription factor, and thus, its function depends on cytoplasmic to nuclear translocation. To discover novel inhibitors of the Stat3 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…There have been several strategies to inhibit the STAT3 pathway as a therapeutic approach in treating cancers, such as by using small molecules and DNA decoys (Lui et al, 2007). In addition, other inhibitors of STAT3 have also been reported including Cucurbitacin Q, which inhibits STAT3 phosphorylation (Sun et al, 2005), E804 that inhibits both Src and STAT3 (Nam et al, 2005); Stattic (Schust et al, 2006) and S3I-201 (Siddiquee et al, 2007), which inhibit STAT3 dimerisation, and SD-1029, which inhibits STAT3 nuclear translocation (Duan et al, 2006). One difficulty with targeting proteins directly is that the targeted proteins may often also control other vital pathways sometimes leading to severe unwanted effects.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several strategies to inhibit the STAT3 pathway as a therapeutic approach in treating cancers, such as by using small molecules and DNA decoys (Lui et al, 2007). In addition, other inhibitors of STAT3 have also been reported including Cucurbitacin Q, which inhibits STAT3 phosphorylation (Sun et al, 2005), E804 that inhibits both Src and STAT3 (Nam et al, 2005); Stattic (Schust et al, 2006) and S3I-201 (Siddiquee et al, 2007), which inhibit STAT3 dimerisation, and SD-1029, which inhibits STAT3 nuclear translocation (Duan et al, 2006). One difficulty with targeting proteins directly is that the targeted proteins may often also control other vital pathways sometimes leading to severe unwanted effects.…”
Section: Discussionmentioning
confidence: 99%
“…The large body of data validating Stat3 as a potential target for cancer therapy, and the tolerance of normal cells to the loss of Stat3 function, has driven the effort to identify molecules capable of Stat3 inhibition (17,25). SD-1029 has been identified as a novel inhibitor of Stat3 activation (26). This molecule blocks Jak activity with resultant inhibition of Stat3 phosphorylation, nuclear transport, and a decrease in Stat3-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule blocks Jak activity with resultant inhibition of Stat3 phosphorylation, nuclear transport, and a decrease in Stat3-dependent transcription. Such actions have culminated in apoptosis in several human breast and ovarian cancer cell lines (26). The activation of Stat3 in chordomas indicates that this pathway may also serve as a potential target for the treatment of these tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…whereas phosphorylated, activated STAT3 translocates to the nucleus to induce gene transcription. 35 Nuclear STAT3 has been found in 70% of ovarian cancers, and is associated with a poor prognosis. 1 Our group has demonstrated that re-expression of ARHI at physiological levels in two different ovarian cancer cell lines inhibited nuclear translocation of STAT3 and suppressed motility.…”
Section: Arhi Decreases β1 Integrin Expressionmentioning
confidence: 99%